Positioning Performance of Power and Manual Drivers in Posterior Spinal Fusion Procedures - J. Micah Prendergast; Alexander C. Perry; Vikas V. Patel; Emily M. Lindley; Mark E. Rentschler (Applied Bionics and Biomechanics)
This work presents an analysis and comparison of the efficacy of two methods for pedicle screw placement during posterior spinal fusion surgery. A total of 100 screws (64 manual and 36 power driven), all placed utilizing a surgical navigation system, were analyzed and compared. Final screw placement was compared to initial surgical plans using the navigation system, and the final screw locations were analyzed on the basis of angular deviation from these planned trajectories as well as screw translation within a critical reference plane. The power driver was found to insignificantly decrease the resulting angular deviation of these pedicle screws with a mean deviation of 3.35 degrees compared to 3.44 degrees with the manual driver (p=0.853). Conversely, the power driver was found to increase the translational distance in the critical region, with mean deviations of 2.45 mm for the power driver compared to 1.54 mm with the manual driver. The increase in translational deviation was significant (p=0.002) indicating that there may be some loss in performance from the adoption of the power driver.